Massive mortality associated with Streptococcus agalactiae Infection in Cage-cultured Red Hybrid Tilapia Oreochromis niloticus in Como River, Kenyir Lake, Malaysia - Najiah, M.; Aqilah, N.I.; Lee, K.L.; Khairulbariyyah, Z.; Mithun, S.; Khan Chowdhury, Ahmed Jalal; Shaharom-Harrison, F.; Nadirah, M. (Asian Network for Scientific Information, 2012)
Massive mortality of cage-cultured red hybrid tilapia Oreochromis niloticus in Como River, Kenyir Lake, Malaysia was investigated. Moribund fish showing erratic swimming, sluggishness and hemorrhagic eyes were collected for the study. Water quality parameters were measured on-site. The highest temperature was 32.70°C at the surface while lower temperature was 30.85°C at 6 m. Dissolved Oxygen (DO) was highest 7.05 mg L-1 at 4 m while lowest 6.15 mg L-1 at 10 m. The pH value was highest 8.28 at 6 m and lowest 7.52 at surface. The result has shown that un-ionized ammonia levels ranged from 0.00046-0.01 ppm within the optimum range. While Nitrite (0.003 ppm) and Nitrate values (0.1-0.7 ppm). The water quality parameters were showed their values within the accepted range of water quality for aquaculture. Bacteria were isolated from diseased fish using blood and nutrient agars, and identified using BBL Crystal™ Enteric/Non-fermenter ID and Gram Positive ID Systems and subjected to antibiotic susceptibility analysis. Results showed the presence of Streptococcus agalactiae, Burkholderia cepacia in the fish liver and Staphylococcus aureus in the fish eyes, suggesting a possible case of warm-water streptococcosis associated with S. agalactiae with multiple bacterial complications. Nevertheless, a continuous long term monitoring is essential for the sustainable development of cage aquaculture in Como river of Lake Kenyir Malaysia.